The Level of Knowledge Regarding Dengue Hemorrhagic Fever - Oktaviana, Elisa (Inspirasi Foundation, 2024)
Objective: The primary objective of this study is to assess the level of knowledge regarding dengue hemorrhagic fever (DHF) within the Tanjung Karang Community Health Center's operational jurisdiction. Method: The research employed an analytical-descriptive approach. The study population comprised individuals residing in the Tanjung Karang Community Health Center area who had encountered dengue fever. The total number of reported dengue fever cases within the Tanjung Karang Community Health Center's operational boundary, spanning six sub-districts from January 2021 to August 2022, amounted to 96 cases. Utilizing the Slovin formula with a margin of error set at 0.05, the calculated sample size was 77. Results: Findings revealed that 39 individuals (50.6%) exhibited sufficient knowledge of preventive measures against DHF. Subsequently, 20 participants (26.0%) demonstrated good knowledge of preventative strategies, while 18 individuals (23.4%) displayed a lower level of awareness regarding DHF prevention efforts. Conclusion: The study findings revealed varying levels of knowledge among participants regarding prevention efforts for dengue hemorrhagic fever. These results underscore the importance of continuous education and awareness initiatives to enhance community knowledge and promote effective prevention strategies.